MONETARY POLICY AS A TOOL FOR ENSURING THE FINANCIAL STABILITY OF THE BANKING SYSTEM AND ECONOMIC SECURITY OF UKRAINE (INNOVATIVE ECONOMY, 2025)
Stetsko M.V.  MONETARY POLICY AS A TOOL FOR ENSURING THE FINANCIAL STABILITY OF THE BANKING SYSTEM AND ECONOMIC SECURITY OF UKRAINEPurpose. The aim of the article is to determine the role and capabilities of monetary policy as a key instrument for ensuring financial stability and economic security in the context of financial sector digitalization, as well as to develop approaches for adapting monetary mechanisms to the emerging challenges of the digital economyMethodology of research. The study employs methods of analysis and synthesis and a systemic approach to reveal the role of monetary policy in ensuring financial stability. A comparative analysis is used to determine the impact of digital technologies and FinTech innovations on the effectiveness of monetary regulation. A forecasting method is applied to identify prospects for adapting monetary policy to the conditions of digital transformation.Findings. The article analyses the role of monetary policy in ensuring financial stability and economic security in the context of digitalization and assesses the impact of digital technologies, FinTech innovations, and central bank digital currencies (CBDCs) on the effectiveness of monetary regulation. Key digital risks (systemic, operational, regulatory, and cyber risks) are systematized, and the interconnection between transmission mechanisms and macroprudential instruments is revealed. Directions for improving Ukraine’s monetary policy are proposed, including integration with macroprudential supervision, the use of big data and AI, enhancing cybersecurity, and developing financial literacy, as a key condition for strengthening the resilience of the banking system and the country’s economic security.Originality. The study further develops the theoretical approach to the role of monetary policy under digitalization, considering it as a comprehensive mechanism for ensuring financial stability and economic security, taking into account the transformation of transmission mechanisms and the need to combine monetary and macroprudential policy amid increasing digital risks.Practical value. The research results can be used by the National Bank of Ukraine to improve monetary and macroprudential policy under digitalization, introduce modern risk-management instruments, and develop strategic approaches to digital development and cybersecurity, as well as by banking institutions to enhance the effectiveness of implementing these policies in their activities.Key words: financial stability, economic security of the state, banking system, stability of banking institutions, central bank, monetary policy, lending, systemic risks and threats, digitalization.
Keywords: financial stability; economic security of the state; banking system; stability of banking institutions; central bank; monetary policy; lending; systemic risks and threats; digitalization